2012
DOI: 10.21157/j.ked.hewan.v6i2.310
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Klinis Sapi Piometra Sebelum Dan Setelah Terapi Dengan Antibiotik Dan Prostaglandin Secara Intra Uteri

Abstract: Penelitian ini bertujuan mengetahui gambaran klinis sapi pyometra sebelum dan setelah diterapi dengan antibiotik dan prostaglandin. Dalam penelitian ini digunakan enam ekor sapi betina yang didiagnosis menderita piometra berdasarkan pemeriksaan secara klinis dan ultrasonografi pada organ reproduksi. Sapi tersebut dibagi ke dalam dua kelompok perlakuan, masing-masing 3 ekor sapi untuk tiap kelompok. Kelompok I diterapi dengan 5 ml antibiotik (gentamicine, flumequine) ditambah 15 ml NaCl fisiologis dan PGF2α (Lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
1
Order By: Relevance
“…Santoso et al (2014) described that persistent corpus luteum often found in cows with reproductive disorders, indicated with continuous progesterone production and longer heat cycle. However, in some cases, cows could still get pregnant, but the fetus would still die to the failure involution (Sayuti et al, 2012;Cuneo et al, 2006). Siregar et al (2012) described that small follicles (3-8) with a total of fewer than 10 follicles are categorized as dominant follicles, while small follicles with a total of more than 10 follicles were not.…”
Section: Relationship Between Non-return Rate Estradiol 17-β Concentmentioning
confidence: 99%
“…Santoso et al (2014) described that persistent corpus luteum often found in cows with reproductive disorders, indicated with continuous progesterone production and longer heat cycle. However, in some cases, cows could still get pregnant, but the fetus would still die to the failure involution (Sayuti et al, 2012;Cuneo et al, 2006). Siregar et al (2012) described that small follicles (3-8) with a total of fewer than 10 follicles are categorized as dominant follicles, while small follicles with a total of more than 10 follicles were not.…”
Section: Relationship Between Non-return Rate Estradiol 17-β Concentmentioning
confidence: 99%
“…Swollen uterine horn with purulent exudate is the characteristic of chronic purulent endometritis or pyometra [19]. Hardjopranjoto [5] added that the thickened uterine wall was caused by scar tissue without tonus in the uterus.…”
Section: Resultsmentioning
confidence: 99%
“…Streptomisin merupakan salah satu contoh bahan bioaktif yang diisolasi dari genus Streptomyces yang kemudian dipakai untuk pengobatan penyakit tuberculosis (TBC) (Buss dan Butler, 2010). Selain itu, Sayuti et al (2012) juga telah melaporkan penggunaan kombinasi antibiotik dan prostaglandin untuk terapi percepatan pengeluaran leleran pada sapi.…”
Section: Pendahuluanunclassified